Does offshoring of materials and business services affect employment? Evidence from a small open economy - Bernhard Michel; François Rycx (Institute for the Study of Labor (IZA), 2009)
The fear of massive job losses has prompted a fast-growing literature on offshoring and its impact on employment in advanced economies. This paper examines the situation for Belgium. It improves the offshoring intensity measure by computing a volume measure of the share of imported intermediates in output and it is among the first to address both materials and business services offshoring to high-wage and low-wage countries. Estimations of static and dynamic industry-level labour demand equations augmented by offshoring intensities do not reveal a significant impact of either materials or business services offshoring on total employment for Belgium between 1995 and 2003.
urn:nbn:de:101:1-20090605213
Keywords: F15; J22; 330; Offshoring; imported intermediate inputs; supply and use tables; industry-level employment; labour demand equations; panel data; Offshoring; Vorprodukt; Unternehmensdienstleistung; Sektorale Beschäftigungsstruktur; Arbeitsnachfrage; Beschäftigungseffekt; Schätzung; Belgien